Analisis Prinsip Good Governance dalam Pelaksanaan Pelayanan Publik di Kantor Desa Kimak Kecamatan Merawang Kabupaten Bangka - Sofi Yulia Sari; Agus Sofyan (SENTRI: Jurnal Riset Ilmiah, 2026)
The study on the Analysis of Good Governance Principles in the Implementation of Public Services in Kimak Village, Merawang District, Bangka Regency is a qualitative descriptive study aimed at providing a real depiction of the service conditions in the village. The instruments used include observation, in-depth interviews, and documentation, with data analysis conducted through the stages of data reduction, data display, and data verification based on primary and secondary data sources. The focus of the research concerns nine criteria for measuring good governance, namely Participation, Legal Supervision, Transparency, Responsiveness, Consensus-Oriented, Justice and Inclusivity, Effectiveness and Efficiency, Accountability, and Strategic Vision. The results indicate that of the nine criteria, five have not been implemented ideally, namely Participation, Rule of Law, Justice and Inclusivity, Effectiveness and Efficiency, and Accountability. The other four criteria have been ideally fulfilled, namely Transparency, Responsiveness, Consensus-Oriented, and Strategic Vision. This study also explicitly examines the consistency between the “Anti-Corruption” predicate attributed to Kimak Village and the actual practice of good governance principles in the implementation of public services in the field. These findings clearly conclude that the achievement obtained by Kimak Village in 2023 as the best village in providing public services at the Bangka Regency level was not measured using the nine criteria established by the United Nations Development Programme (UNDP).